Effect of pulmonary endarterectomy on six-minute walking test and echocardiography in the early stage - YILDIZELİ, BEDRETTİN; MUTLU, BÜLENT; SÜNBÜL, MURAT (TURKISH SOC CARDIOLOGY, 2016)
Objective: Pre- and postoperative changes in echocardiographic parameters and results of 6-minute walking test (6-MWT) were investigated in the present study. Methods: Seventy-six patients (32 males, 44 females; mean age 45.9 +/- 15.1 years) were included. Before and after surgery, 6-MWT and echocardiography were performed. Changes in postoperative parameters were compared to basal walking test and other basal parameters. Results: Distance covered in 6-MWT significantly increased after surgery (p<0.001). Significant decrease in right ventricular diameter and pressure, and significant increase in left ventricular diameter were also observed. While changes in ejection fraction (EF) were not significant, significant reduction in systolic pulmonary artery pressure (sPAP) and tricuspid regurgitation were observed. No statistically significant correlation was observed between baseline 6-MWT results and echocardiographic parameters. Conclusion: The present study was the first to investigate the correlation between baseline 6-MWT results and right ventricular echocardiographic parameters. Myocardial performance index (MPI) and TAPSE were important parameters in follow-up after pulmonary endarterectomy. Improvement in quality of life parameters was also important.
Keywords: Chronic thromboembolic pulmonary hypertension; pulmonary endarterectomy; right heart failure; VENTRICULAR FUNCTION; LUNG-FUNCTION; HYPERTENSION; THROMBOENDARTERECTOMY; DISPLACEMENT